Ijtihad dan Fatwa Sebagai Solusi Persoalan Keagamaan di Era Kontemporer - Muchtar, Nurkhalis (PT. Student Rihlah Indonesia, 2025)
The complexity of modern life requires relevant legal guidelines. The Prophetalso emphasized the authority of ijtihad as a method of interpreting Islamic lawderived from the Qur'an and Sunnah. Because only through ijtihad can Islam remainrelevant to the times, as ijtihad is the spirit of Islam. The purpose of this research is to analyze ijtihad and fatwa as solutions to religious issues in the contemporary era. This research uses a qualitative descriptive research method on library data findings, with a library research and content analysis approach.The conclusion of this research finds that Islamic law experts have made serious efforts in ijtihad and fatwa, as reflected in the various scientific contributions they have made. This research also explains that Islamic law experts have made serious efforts in ijtihad and fatwa, as reflected in the various scientific contributions they have made. The conclusion of this research finds that Islamic law experts have made serious efforts in ijtihad and fatwa, as reflected in the various scientific contributions they have made. This research also explains that Islamic law experts have made serious efforts in ijtihad and fatwa, as reflected in the various scientific contributions they have made.analysis. The conclusion of this study finds that Islamic legal experts havemade serious efforts in ijtihad and fatwa, asreflected in the various scientific contributions they have made. This studyalso explains the various efforts of contemporary scholars who are trying to actualizeijtihad in the present era, so that Islam can be seen as a solution forhumanity in various aspects of life.